Immersion for Entangled Audiences: The Nonhuman World and Affective Patterning in Narrative Experiences - Caracciolo, Marco (Kinephanos, 2020)
The language of “immersion” in a fictional text lends itself to a dualistic reading that is, at best, unwelcome when attempting to think about narrative experiences ecologically. In this article, I argue for a model of narrative-audience interactions that privileges immersion as affective and temporal entanglement in stories over the containment model. I use Le quattro volte, a 2010 film by Italian director Michelangelo Frammartino, to exemplify this alternative understanding of audiences’ engagement with narrative and discuss its ramifications for recent work at the intersection of narrative theory and ecocriticism.